Does Student Motivation and Teaching Presence Influence Academic Performance? Examining The Role of Cognitive Presence - F. Pambudi Widiatmaka (International Conference on Science, Education, and Technology, 2021)
Motivation is an essential aspect of the learning process. Internal motivation is an impulse that arises from students, therefore it becomes an important aspect to elaborate. This study attempt to analyze the effect of motivation and teaching presence on students' cognitive presence and academic performance. This research was conducted on student officers at the Merchant Marine Polytechnic of Semarang by using a quantitative approach involving SEM Amos to analyze the data. The results showed that motivation had a positive and significant effect on academic performance. In addition, cognitive presence mediates the influence of motivation on academic performance. The results of this study indicate that academic performance first through the presence of cognitive to obtain satisfactory academic results. These results are obtained through a process or encouragement that arises from within the students. The learning process is also influenced by the lecturer's support so that the lecturer's contribution in the learning process has an important influence in determining students' academic performance. The results of this study indicate that teaching presence influences cognitive presence and academic performance. This study confirms that there is an important role for lecturers to provide an increase in students' cognitive competence and academic performance. Lecturers are facilitators who can manage a class, so that management will lead to the rise in academic competence which also affects academic performance.